Optimization and improvement of recombinant chitinase biosynthesis in E. coli using response surface method - Thu Ha, Trinh Thi; Quyen, Dong Van; Binh, Ngo Dinh (Academia Journal of Biology, 2017)
Chitinases (EC 3.2.1.14) are enzymes that degrade chitin. These enzymes are gaining importance for their wide-ranging applications including the preparation of pharmaceutically important chitooligosaccharides and N-acetyl D glucosamine, preparation of single-cell protein, isolation of protoplasts from fungi and yeast, control of pathogenic fungi, treatment of chitinous waste, mosquito control and morphogenesis and especially in agriculture fields to control pathogens. Previously, we have cloned chiA gene encoding chitinase for overexpresion in E. coli. Herein, we optimized the expression conditions for improvement of chitinase biosynthesis in recombinant E. coli strain using response surface method (RSM) based on Design-Expert 10.1 software (Stat-Ease, Inc., Minneapolis, USA. Fermentation conditions such as inducer concentrate, induction time and cell density at the time of induction and their effects on the chitinase biosynthesis were investigated. The RMS analysis suggested that the optimal conditions for production of recombinant ChiA are at lactose concentration of 6,15 mM, 8,12 hours after induction and cell density OD600nm = 0,87 with predicted enzyme activity of 7,49 U/ml. The model obtained was used for fermentation of recombinant strain and the real chitinase activity achieved 7,54 U/ml which is 1.32 times higher compared to that of the pre-optimization (5.71 U/ml). The RSM was found to be useful in optimizing and determining the interactions among process variables in ChiA enzyme production. Our data also indicated that using lactose as the inducer instead of ITPG for ChiA expression can also reduce product costs. Citation: Trinh Thi Thu Ha, Dong Van Quyen, Ngo Dinh Binh, 2018. Optimization and improvement of recombinant chitinase biosynthesis in E. coli using response surface method. Tap chi Sinh hoc, 40(1): x-xx. DOI: 10.15625/0866-7160/v40n1.10495. *Corresponding author: binh.gen@gmail.com Received 5 July 2017, accepted 20 December 2017